Social Policies and Institutional Reform in Post-COVID Cuba - Hoffmann, Bert (Verlag Barbara Budrich, 2021)
Die tiefe Wirtschaftskrise in Folge der Corona-Pandemie stellt Kubas Sozialismus vor eine ungeahnte Belastungsprobe. Die Regierung in Havanna hat eine grundlegende Reform von Wirtschaft, Institutionengefüge und Sozialsystem auf die Agenda gesetzt. Der Band vereint Beiträge führender internationaler Experten und von der Insel selbst, die aus unterschiedlichen Perspektiven die Herausforderungen analysieren, vor denen Kuba heute steht.; The economic crisis in the wake of the COVID pandemic is putting Cuba's socialism to a severe test. The government in Havana has added a fundamental reform of the economy, institutional structure and social policies to the agenda. This volume brings together contributions from leading international experts as well as from the island itself, analysing the economic, political and social challenges Cuba is facing today.